Sobre outras revoluções possíveis: o lazer e a festa como forma de resistência nas ocupações urbanas da Izidora - Izabella Galera (2019)
This research seeks to raise the discussion about leisure practices as a form of resistance to the hegemonic production of urban space, based on the experience of Izidora Urban Occupations in Belo Horizonte / MG, unveiling here other elements inserted in the middle of the struggle for housing, pointing to a struggle for the right to urban life, for the right to laugh and be happy in the city. This research is anchored in experiencing and reflecting on leisure in occupations, mapping the production of space through plays, parties and games in territories that are in the midst of an emblematic urban conflict that disrupted a millionaire project that was planned for the region. These spatial practices are supported by popular knowledge that even without institutional support that guarantees access to basic rights for a dignified life, put in manifestation other forms of production of the space constructed daily. Along with the occupations of Rosa Leão, Esperança, Vitória and Helena Greco in the region of Izidora, the spontaneous leisure practices were verified and where these are territorialized, thus participating in the most pleasant and pleasurable part of life. It is understood here that the plays, the laughter and the party have the capacity to humanize the city, claiming it for its use value, being counterproductive and, therefore, with the power to dissolve the hegemonic forms of production of the city. Being an essential part of life, spontaneous play encompasses the notion of autonomy, freedom, subversion, playful attitude, popular cultures and time-space. In crossing these dimensions, mainly understanding who, where and how they are practiced, leisure is defended as a joyful form of resistance and revolutionary because it is free, to act in the bodies, in the imaginary in subjectivity and intersubjectivity.